Antibiotic eluting poly(ester urea) films for control of a model cardiac implantable electronic device infection. (15th July 2020) - Nikam, Shantanu P.; Nettleton, Karissa; Everitt, Jeffrey I.; Barton, Hazel A.; Becker, Matthew L.
Abstract: Cardiac implantable electronic device (CIED) infections acquired during or after surgical procedures are a major complication that are challenging to treat therapeutically, resulting in chronic and sometimes fatal infections. Localized delivery of antibiotics at the surgical site could be used to supplement traditional systemic administration as a preventative measure. Herein, we investigate a cefazolin-eluting l -valine poly(ester urea) (PEU) films as a model system for localized antibiotic delivery for CIEDs. Poly(1-VAL-8) PEU was used to fabricate a series of antibiotic-loaded films with varied loading concentrations (2%, 5%, 10% wt/wt) and thicknesses (40 µm, 80 µm, 140 µm). In vitro release measurements show thickness and loading concentration influence the amount and rate of cefazolin release. Group 10%-140 µm (load-thickness) showed 22.5% release of active pharmaceutical ingredient (API) in the first 24 h and 81.2% of cumulative percent release through day 14 and was found most effective in bacterial clearance in vitro . This group was also effective in clearing a bacterial infection in a model in vivo rat study while eliciting a limited inflammatory response . Our results suggest the feasibility of cefazolin-loaded PEU films as an effective sustained release matrix for localized delivery of antibiotics. Significance Statement: Implant-associated infections acquired during surgical procedures are a major complication that have proven a challenge to treat clinically, resulting in chronic and sometimes fatal infections. In this manuscript, we investigate an antibiotic-eluting L-valine poly(ester urea) (PEU) films as a model system for localized delivery of cefazolin. Significantly, we demonstrate a wide variation in temporal delivery and dosing within this family of PEUs and show that the delivery can be extended by varying the film thickness. The in vivo results show efficacy in an infected wound model and suggest antibiotic loaded PEU films function as an effective sustained release matrix for localized delivery of antibiotics across a number of clinical indications. Graphical abstract: Image, graphical abstract